Hemocompatibility improvement of decellularized spleen matrix for constructing transplantable bioartificial liver. (4th January 2019) - Liu, Peng; Tian, Boyan; Yang, Lifei; Zheng, Xinglong; Zhang, Xufeng; Li, Jianhui; Liu, Xuemin; Lv, Yi; Xiang, Junxi
Abstract: Thrombogenicity is the predominant obstacle to successful implantation of decellularized spleen matrix (DSM). The aim of this study was to construct a transplantable functional bioartificial liver (BAL) with the use of DSM. This was achieved by layer-by-layer electrostatic immobilization technique by using poly dimethyl diallyl ammonium chloride and heparin. After heparin immobilization, DSM gradually turned from translucent into completely opaque milky white. Toluidine blue staining showed strong positive staining of the entire coated DSM. In vitro diluted blood perfusion test showed that the splenic arterial pressure of the heparin-coated DSM was much lower than that of the non-coated DSM ( p < 0.01). Then, we heterotopically transplanted the modified DSM into rat hepatic injury model for 6 h to evaluate the hemocompatibility in vivo . Overall, HE staining and vWF immunohistochemistry all confirmed that heparin-coated DSM has a satisfactory anticoagulant effect. Based on the heparin-coated DSM, BALs were built with the use of rat primary hepatocytes. Our results demonstrate that these heparin-coated BALs satisfied anticoagulant effects even after 6 h. Immunofluorescence of ALB and G6PC also showed that hepatocytes in heparin-coated BAL have significantly higher cell viability and function than the non-coated group. However, serum analysis did not indicate a significant difference between the two groups but a slight trend of improvement with respect to serum albumin ( p  = 0.156) and aspartate transaminase ( p  = 0.140). In conclusion, we demonstrated that the BAL constructed by heparin-coated DSM can exert satisfactory short-term anticoagulant effects and can compensate for a certain degree of liver function.